Induced mutation for cowpea severe mosaic virus resistance and seed coat color in cowpea - Albertoni, Márcia Regina; Araújo, João Pratagil Pereira de; Watt, Earl Eugene (Pesquisa Agropecuaria Brasileira, 2014)
To obtain a commercial variety of cowpea (Vigna unguiculata) resistant to Cowpea Severe Mosaic Virus (CpSMV), seeds of an immune variety 'CNC 0434' were treated with 25 kR and 30 kR of gamma rays from a 60 Co source, In the M1 generation, five different groups of seed-coat color plus the original seed type were identified. These groups segregated in the M2generation with 189 CpSMV resistant plants within 31 different groups of seed-color and high seed-weight variability. Notes on morphological mutants were also taken. From the analysis in the M2, it was concluded that a single recessive gene controls resistance to CpSMV.